Dinâmica das infecções naturais por Eimeria spp em cordeiros da raça Santa Inês criados em sistema semi intensivo no norte de Minas Gerais e seu controle através da administração de toltrazuril - Talita Pinheiro Goncalves da Silva (2006)
The Eimeria spp infection in lactating lambs and the prophylactic efficacy oftoltrazuril against it were evaluated in a semi-intensive system of ovinebreeding, where there was the Santa Inês breed, at the north of Minas Gerais.The first appearance of oocysts of Eimeria spp in lambs faeces was detectedand the evolution of the infection in naturally affected lambs was studiedincluding the identification of the infecting species. The efficacy of toltrazuril(Baycox12) in preventing coccidiosis in lactating lambs was also studied. Fortythree lambs were divided into four groups treated with 20mg of toltrazuril atdifferent ages: Group 1 was treated once when the lambs were four weeks old,group two was treated twice, when the lambs were four and eight weeks old,group three was not treated at all (control group) and the lambs of group 4 weretreated when they were two weeks old. The oocysts were first detected inlambs faeces when they were 16 days old, but it varied between 16 and 32days old lambs. The species most frequently found was E. ovinoidalis (52,8%).The naturally infected lambs OPG (group 3) became positive after they werethree weeks old. The oocyst output of this group of animals progressively roseuntil it peaked when the lambs were seven weeks old, at the 8th week it sharplyreduced and began rising again until a second and smaller peak happened atthe 10th week followed by a more gradual and consistent reduction in oocystcounting. These OPG reductions after the two peaks suggest the developmentof lambs immunity, which was more solid after the second peak. Mixedinfections predominated, eleven Eimeria species were observed during thewhole study period and in some samples nine species could be identified at thesame time. The species infecting the lambs varied individually. E. crandallis wasthe most frequent species found (47,25%). The lambs of the control group hadthe highest oocysts output when compared to the treated groups (P<0,05). Theaction of toltrazuril was influenced by the age of treatment, effectively reducingthe oocyst output for four weeks when administered earlier at the second weekof lambs life (group 4). Lambs of all treated groups developed normal immunity.There was no significance between the weight gains of the four groups. On theother hand, toltrazuril was highly efficient in reducing total oocyst excretion,which happened for three to four weeks after treatment (P<0,05), also reducingthe environments contamination and the lambs challenge